Effect of casein phosphopeptide-amorphous calcium phosphate (cpp-acp) on caries-like lesions in terms of time and nano-hardness: An in vitro study - Shanthan Mettu; Namineni Srinivas; C H Reddy Sampath; Nallanchakrava Srinivas (Wolters Kluwer Medknow Publications, 2015)
Context: Time bound increase in the nanohardness of the enamel after remineralization with casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) in a regular interval of 1 h has not been explored in the literature to a greater extent. Aims: To determine and compare the maximum hardness of the remineralized caries-like lesions, in terms of nanohardness and the rate of achieving maximum hardness at 1-h interval, after treatment with artificial saliva and CPP-ACP, over 12 h. Materials and Methods: Fifty longitudinal sections of extracted sound permanent maxillary central, lateral incisors were immersed in demineralizing solution for 4 days. The samples were then randomly divided into three groups, consisting of 12 sections each for soaking them in three different media-isotonic saline, artificial saliva, and CPP-ACP for 12 h. The nanohardness was measured on the labial surface, at baseline, after erosion, and after remineralization at 1-h interval. Statistical Analysis Used: The data was analyzed with paired t-test, one-way analysis of variance (ANOVA) and post-hoc analysis. Results: CPP-ACP increased the enamel hardness significantly (P < 0.001), at an increased rate, than artificial saliva. Conclusions: This study has provided an insight into the frequency of use of CPP-ACP, once per day, as the nanohardness of enamel samples increased within 1 h of application and remained within the normal limits after 12 h.